2012
DOI: 10.7314/apjcp.2012.13.7.3443
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Breast Cancer Screening Uptake: A Pre Intervention Community Survey in Malaysia

Abstract: Introduction: Despite health education efforts to educate women on breast cancer and breast cancer screening modalities, the incidence of breast cancer and presentation at an advanced stage are still a problem in Malaysia. Objectives: To determine factors associated with the uptake of breast cancer screening among women in the general population. Methods: This pre-intervention survey was conducted in a suburban district. All households were approached and women aged 20 to 60 years old were interviewed with pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 20 publications
6
48
1
1
Order By: Relevance
“…In this study 27.3% of the women who practiced BSE did it correctly, monthly in contrast to 46.7-55.6% in Taiwan, Malaysia and other countries (Feldman;1981;Dahlui et al, 2012;Wu et al, 2012). But,66.3% of the women who reported doing BSE did it only sometimes indicating the need for sustained, high quality educational programmes.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In this study 27.3% of the women who practiced BSE did it correctly, monthly in contrast to 46.7-55.6% in Taiwan, Malaysia and other countries (Feldman;1981;Dahlui et al, 2012;Wu et al, 2012). But,66.3% of the women who reported doing BSE did it only sometimes indicating the need for sustained, high quality educational programmes.…”
Section: Discussioncontrasting
confidence: 72%
“…There are contrasting results on association with age in the literature. Hospital and community based survey in Malaysia did not find a relationship with age (Dahlui et al, 2012;Subramaniam et al, 2013) whereas in Taiwan (Wu et al, 2012), older women were more likely to undergo screening and another study showed a higher probability of screening among younger women. In this study after multiple logistic regression age was found to be an independent predictor of breast cancer screening (Hackshaw and Paul, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…The majority of the studies determined the level of knowledge of breast cancer among Malaysian women based on several aspects such as general knowledge of breast cancer, causes, risk factors, symptoms of breast cancer and screening tests (Abdul-Hadi et al, 2010b;Khan et al, 2010;Akhtari-Zavare et al, 2011;Dahlui et al, 2012;Che et al, 2014;Yusof et al, 2014). Overall, females in Malaysia had a good awareness of breast cancer (AbdulHadi et al, 2010b;Khan et al, 2010;Akhtari-Zavare et al, 2011;Dahlui et al, 2011;Dahlui et al, 2012;Che et al, 2014;Yusof et al, 2014).…”
Section: Knowledge Of Breast Cancermentioning
confidence: 99%
“…Overall, females in Malaysia had a good awareness of breast cancer (AbdulHadi et al, 2010b;Khan et al, 2010;Akhtari-Zavare et al, 2011;Dahlui et al, 2011;Dahlui et al, 2012;Che et al, 2014;Yusof et al, 2014). Most respondents indicated that they heard about breast cancer mainly from sources such as books, magazines, brochures and television (Parsa and Kandiah, 2010;Al-Dubai et al, 2011;Akhtari-Zavare et al, 2013).…”
Section: Knowledge Of Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation